Valuing Films
XI, 228 p.
Keywords: This volume gets to the heart of what films mean to people on personal, political and commercial levels. Exploring value judgements that underpin social, academic and institutional practices, it examines the diverse forms of worth attributed to a range of international films in relation to taste, passion, morality and aesthetics.